Polydatin attenuates Alzheimer’s disease induced by aluminum chloride in rats: evidence for its antioxidant and anti-inflammatory effects - Zarneshan, Seyede Nazanin; Fakhri, Sajad; Kiani, Amir; Abbaszadeh, Fatemeh; Hosseini, Seyede Zahra; Mohammadi-Noori, Ehsan; Echeverría, Javier (Frontiers in Pharmacology, 2025)
BackgroundConsidering the complex pathophysiological mechanisms behind Alzheimer’s disease (AD), a few drugs for managing related cognitive symptoms have been approved. The phytochemical resveratrol has shown promising anti-inflammatory and antioxidant effects in AD, but it has low bioavailability. Chemical modification of resveratrol to its glycosylated form, polydatin (PD), significantly increases its bioavailability and bioactivity.PurposeThe study aimed to investigate the therapeutic potential and mechanisms of action of PD against AD in rats.Material and methodAD was caused by an intraperitoneal (i.p.) administration of aluminum chloride (AlCl3). Six groups of six rats each were defined as sham, negative control (AlCl3), positive control (Donepezil), and treatments (PD 5, 10, and 20 mg/kg, i.p.). On days 7, 8, 14, and 15, the rats’ behavioral changes were assessed by the open field, Y-maze test, passive avoidance test, and elevated plus maze tests. At the end of the study, the blood samples were collected to assess the levels of glutathione (GSH), catalase (CAT), and nitrite, as well as the activity of matrix metalloproteinases (MMPs). Furthermore, hippocampal brain tissue was removed and used for histological investigations.Results and discussionThe findings revealed that PD injections at three different doses (5, 10, and 20 mg/kg) improved cognitive and other behavioral impairments. Furthermore, PD improved the antioxidant capacity by increasing GSH and CAT while decreasing serum nitrite levels. PD showed anti-inflammatory effects by reducing the activity of inflammatory MMP-9, while elevating the activity of anti-inflammatory MMP-2. PD also modulated pathogenic changes in the hippocampal brain tissue.ConclusionPD alleviated cognitive and other behavioral impairments in AD rats by enhancing antioxidant defenses and reducing neuroinflammation.